Generative complexity in algebra - Berman, Joel, 1943- (Memoirs of the American Mathematical Society ;, 2005)
Introduction Background material Part 1. Introducing Generative Complexity: Definitions and examples Semilattices and lattices Varieties with a large number of models Upper bounds Categorical invariants Part 2. Varieties with Few Models: Types 4 or 5 need not apply Semisimple may apply Permutable may also apply Forcing modular behavior Restricting solvable behavior Varieties with very few models Restricting nilpotent behavior Decomposing finite algebras Restricting affine behavior A characterization theorem Part 3. Conclusions: Application to groups and rings Open problems Tables Bibliography.